Protocols for Visually Guided Navigation Assessment of Efficacy of Retina-Directed Cell or Gene Therapy in Canines - Aravand, Puya; Ramachandran, Pavitra S.; Schpylchak, Ivan; Phelps, Nicholas T.; Nikonov, Sergei; Bennett, Jean (Frontiers in Neuroscience, 2017)
There has been a marked progress in recent years in developing gene delivery approaches for the treatment of inherited blinding diseases. Many of the proof-of-concept studies have utilized rodent models of retinal degeneration. In those models, tests of visual function include a modified water maze swim test, optokinetic nystagmus, and light-dark activity assays. Test paradigms used in rodents can be difficult to replicate in large animals due to their size and awareness of non-visual aspects of the test system. Two types of visual behavior assays have been utilized in canines: an obstacle avoidance course and a forced choice Y maze. Given the progress in developing cell and gene therapies in large animals, such tests will become more and more valuable. This study provides guidelines for carrying out such tests and assesses the challenges and benefits associated with each test.